Processing optimization and characterization of gelatin from catfish (Clarias gariepinus) skin - Ardekani, V. Sanaei; Mahmoodani, F.; See, S.F.; Yusop, S.M.; Babji, A.S. (Universiti Kebangsaan Malaysia, 2013)
The extraction of catfish (Clarias gariepinus) skin gelatin was optimized by using response surface methodology (RSM) employing a central composite design (CCD). RSM with 3-factors, 5-levels CCD was carried out for the optimization. The independent variables were suggested which include NaOH concentration (0.07-0.23 mol/L), acetic acid concentration (0.04-0.14 mol/L) and extraction temperature (40-80°C) with the percentage of hydroxyproline recovery (Y) as dependant variable. A maximum Y of 65.32% for gelatin processing was obtained using a combination of 0.13 mol/L NaOH and 0.09 mol/L acetic acid for 1 h, followed by a hot-water extraction at 64.92°C for 3 h. The results indicated a high protein content (88.46 g/100 g) in the extracted gelatin with a viscosity of 3.45 mPa.s, 286.71 g gel strength and 173 residues per 1000 residues of imino acids (proline and hydroxyproline). Furthermore, the gelatin from catfish also showed a relatively good instrumental texture quality according to texture profile analysis (TPA).